Uncovering Hidden Realities: A Phenomenological Approach to Financial Crime in Public Procurement - Parintak, Sutrisno (Journal of International Conference Proceedings, 2023)
This research aims to uncover the hidden reality of financial crime in the context of public procurement using a phenomenological approach. Through in-depth analyses of the experiences of financial criminals, procurement officials, and the communities involved, the research identifies the factors that drive fraud in the procurement process. The results show that the complexity of the procurement system, local social, economic and cultural pressures play a key role in the dynamics of financial crime. Dissatisfaction with complex procurement procedures and pressure to achieve a certain status are the main triggers for fraud. The implications of this research underscore the need for reforms in the procurement system, increased transparency and accountability. Practical suggestions involve additional education and training for procurement officials, addressing social pressure through social programs, and strengthening internal and external oversight. By highlighting the long-term impact of fraud in public procurement, this research provides a basis for policy and practice changes to create an environment of greater integrity and efficiency in the use of public funds. Collaboration with stakeholders, including researchers and academics, was identified as a strategic step towards achieving this goal.